Pengembangan Media Pembelajaran Teks Negosiasi Berbasis Audio Visual Untuk Siswa Kelas X SMA Swasta Al-Hidayah Medan - Br Perangin-angin, Santi Julpita; Ali, Ali; Amaluddin, Amaluddin (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This research aimed to develop audio-visual-based learning media for negotiating texts using the CapCut application for Class X students at SMAS Al-Hidayah Medan. The objectives were to assess the feasibility and effectiveness of the developed learning media. The study followed the Thiagarajan 4-D model: defining, designing, developing, and disseminating. Material experts evaluated the media and deemed it decent with a score of 73.5%. Design experts rated it very decent with a score of 90%. The media was then tested on Indonesian language teachers and Class X(1) students, receiving high ratings of 95% and 92% respectively. The data indicated the validity and feasibility of the learning media. Students' scores increased after using the media, reaching the minimum passing grade. Consequently, the audio-visual-based negotiating text learning media was deemed both feasible and effective for the learning process.